2015
DOI: 10.1371/journal.pone.0135026
|View full text |Cite
|
Sign up to set email alerts
|

What’s a Weed? Knowledge, Attitude and Behaviour of Park Visitors about Weeds

Abstract: Weeds are a major threat to biodiversity globally degrading natural areas of high conservation value. But what are our attitudes about weeds and their management including weeds in national parks? Do we know what a weed is? Do we consider weeds a problem? Do we support their management? Are we unintentionally spreading weeds in parks? To answer these questions, we surveyed visitors entering a large popular national park near the city of Brisbane, Australia. Park visitors were knowledgeable about weeds; with >7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…An EWRR relies heavily on people's knowledge about IAS, which, according to several studies (Ansong and Pickering 2015;Carlson and Vondracek 2014;Ford-Thompson et al 2015;Nanayakkara et al 2018;Sharp et al 2011), can affect their capacity to participate in managing IAS and therefore successfully implement the system. In our research, the media obviously plays a key role in informing the public about IAS and, as confirmed by Marzano et al (2015), significantly contributes to the public's understanding of IAS related issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An EWRR relies heavily on people's knowledge about IAS, which, according to several studies (Ansong and Pickering 2015;Carlson and Vondracek 2014;Ford-Thompson et al 2015;Nanayakkara et al 2018;Sharp et al 2011), can affect their capacity to participate in managing IAS and therefore successfully implement the system. In our research, the media obviously plays a key role in informing the public about IAS and, as confirmed by Marzano et al (2015), significantly contributes to the public's understanding of IAS related issues.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published on the attitudes of the public towards alien species and possible management measures (Ansong and Pickering 2015;Fischer and Charnley 2012;Ford-Thompson et al 2015;Lindemann-Matthies 2016;Nanayakkara et al 2018;Porth et al 2015;Rolfe and Windle 2014;Subroy et al 2018;Verbrugge et al 2013). However, most of these studies focused on only one taxonomic group-similar to the findings of Courchamp et al (2017)-from which the invasive plant species were best studied.…”
mentioning
confidence: 99%
“…Hence, the AIWs may be closer to equilibrium in the invasive range than in the native range (Callen & Miller, ; Early & Sax, ; Strubbe, Broennimann, Chiron, & Matthysen, ). Niche divergence is strongly related to rapid evolution in the invasive range, disequilibrium in the native range caused by biotic interactions, dispersal barriers, and human activities (Ansong & Pickering, ; Dellinger et al., ; Guo, Lambertini, Li, Meyerson, & Brix, ; Lötter & Maitre, ; Marini et al., ; Martínez‐Cabrera, Schlichting, Silander, & Jones, ; Schmidt & Drake, ). Previous studies have shown that plant species for which dispersal ability is limited in native ranges could occupy wide climatic niche spaces enabled by genetic evolution and human activities (Donoghue & Edwards, ; Dellinger et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Alien invasive weeds (AIWs) have a high potential to threaten plant diversity (Ansong & Pickering, ; Beaumont, Gallagher, Leishman, Hughes, & Downey, ; van Kleunen et al., ; Parker, ; Stratonovitch, Storkey, & Semenov, ). By altering ecosystem functioning, the uncontrolled expansion of AIWs may also cause severe crop yield losses (Chauhan, Singh, Kumar, & Johnson, ; Fahad et al., ; Parker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Support for management efforts can markedly increase when focus group discussions with stakeholders relay the rationale and methodology of invasive species eradication (Bremner and Park 2007). Findings suggest that stakeholders' knowledge about invasive species can influence their prevention, spread, and control, both through direct public action and support for management strategies (Ansong and Pickering 2015;Carlson and Vondracek 2014;Ford-Thompson et al 2015;Sharp et al 2011).…”
Section: Introductionmentioning
confidence: 99%